Increasing Einvite.id's Brand Awareness To Boost Sales - Marmaiyatno, Marmaiyatno; Halim, Deddy Kurniawan; Vivi, Vivi; Mulia, Victor Bangun; Hollandina, Ni Putu Darla (Journey : Journal of Tourismpreneurship, Culinary, Hospitality, Convention and Event Management, 2025)
This research focuses on PT. Einvite Karya Sejahtera, the owner of the Einvite.id brand, which provides digital invitation and digital guestbook services. Although the product was popular during the pandemic, intensified competition and a lack of brand awareness have led to a decline in sales. The purpose of this project is to explore strategies to increase brand awareness and strengthen Einvite.id's position in the market. This analysis uses qualitative methods, including interviews and observations, as well as SWOT analysis to identify internal and external factors that affect brand awareness. The findings of this research are three best alternative solutions to grow Einvite.id's brand awareness and increase sales: a. Increase marketing and development efforts by hiring the required staff, b. Sponsor events that are relevant to the target market, c. Maintain flexibility in the use of additional operational teams.